Improvement of the process of hydrothermal treatment and peeling of spelt wheat grain during cereal production - Liubych, Vitalii; Novikov, Volodymyr; Polianetska, Iryna; Usyk, Serhii; Petrenko, Vasyl; Khomenko, Svitlana; Zorunko, Viktor; Balabak, Oleksandr; Moskalets, Valentyn; Moskalets, Tatiana (Eastern-European Journal of Enterprise Technologies, 2019)
The influence of hydrothermal treatment (grain moistening, steeping) and peeling duration on the yield and quality of spelt wheat cereal was studied. The mechanism of the influence of the studied factors on the formation of cereal and culinary quality of the product was established. A comparative analysis of the yield and quality of cereals after hydrothermal treatment at actual humidity content from 13.0 to 14.0 % was performed. Due to the hydrothermal treatment, the properties of the endosperm and shells change significantly. This leads to an increase in the strength of endosperm and formation of higher yield of the finished product. The influence of peeling duration and hydration gradient on the yield of cereal and middling is reliable. The influence of duration of spelt wheat steeping on this process was insignificant. Application of grain damping (humidity content of 15.0–16.0 %) makes it possible to increase the yield of cereal from 88.6 % to 91.7 %. Culinary quality does not change in this case. The obtained mathematical models of the influence of damping steeping, peeling of grain on the yield and quality of cereals are linear. Their accuracy is proved by the high determination coefficients (R2=0.97‒0.98) and by the absence of autocorrelation of residues. In the technology of production of cereals from spelt wheat the recommended method of hydrothermal treatment implies its damping up to 15.0 % of moisture content, which makes it possible to increase the yield of cereals by 3.1 %. The difference from the classical method is the absence of the grain steeping phase before peeling. Damping of spelt wheat grain up to 15.0 % with peeling duration of 160 s is optimum. The proposed way of treatment allows getting 86.5 % of cereals with culinary quality of 8–9 points. The developed recommendations may be used by food industry enterprises during conducting marketing activities or production intensification.